SISTEM PERINGATAN DINI BANJIR AIR LAUT MENGGUNAKAN SENSOR ULTRASONIK MELALUI KOMUNIKASI SMS - Muhammad Rusdi; Febrin Aulia Batubara (Lembaga Penelitian dan Pengabdian (LPPM) STMIK Pelita Nusantara Medan, 2019)
Seawater flood early warning system serves to inform the public of the occurrence of flood events caused by rising sea water. With an early prevention system, the occurrence of sea water floods can reduce the impact or loss caused by tidal floods. This research aims to make a prototype of an early warning system for tidal flooding. Arduino-based systems use ultrasonic sensors to measure sea water levels. The system is also equipped with a buzzer that serves as an alarm to inform the public of a tidal flood. In addition, an early warning for tidal floods will also be delivered to the public through the SMS (Short Message Service) communication media. From the results of the discussion it was found that the early warning system for seawater flooding using two ultrasonic sensors through the SMS communication media works well. The ultrasonic sensor used is able to measure the height (level) of the water surface from 5 cm to 60 cm. The average percentage of measurement error for the first ultrasonic sensor is 1.125% and for the second ultrasonic sensor is 1.515%. The average percentage of measurement error for both sensors is 1.32%. The level of accuracy of system in measuring the height (level) of the water surface is 98.68%.